2020
DOI: 10.1364/oe.391471
|View full text |Cite
|
Sign up to set email alerts
|

Towards Monte Carlo simulation of X-ray phase contrast using GATE

Abstract: We describe the first developments towards a Monte Carlo X-ray phase contrast imaging simulator for the medical imaging and radiotherapy simulation software GATE. Phase contrast imaging is an imaging modality taking advantage of the phase shift of X-rays. This modality produces images with a higher sensitivity than conventional, attenuation based imaging. As the first developments towards Monte Carlo phase contrast simulation, we implemented a Monte Carlo process for the refraction and total reflection of X-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…A method 20 developed by Langer et al was used to simulate phase contrast tomography. The first step consists in using a ray casting procedure in the voxellized object, from which the integral of the refractive index after passing through the object can be obtained.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A method 20 developed by Langer et al was used to simulate phase contrast tomography. The first step consists in using a ray casting procedure in the voxellized object, from which the integral of the refractive index after passing through the object can be obtained.…”
Section: Methodsmentioning
confidence: 99%
“…refraction and scattering) have been implemented in Gate 18 and in Geant-4 19 . In this work, we focused on phase contrast (Fresnel diffraction), therefore, a method proposed by Langer et al 20 using a ray casting procedure to obtain integral of the refractive index, as well as an analytical wave optics approach for generating Fresnel diffraction patterns is used to simulate phase contrast tomography. The implementation is in the GATE software (version 8.2 and later).…”
Section: Introductionmentioning
confidence: 99%
“…Refractive indices are calculated using Xraylib (Schoonjans et al, 2011), integrated in GATE for this purpose (Langer et al, 2020). X-ray particles propagation is step-bystep in the usual Monte Carlo way.…”
Section: Monte-carlomentioning
confidence: 99%
“…Contrary to the wave optics approach, Monte Carlo simulation is based on particle tracking and can correctly simulate attenuation, refraction, and scattering (Bottigli et al, 2004;Peter et al, 2014;Langer et al, 2020). Some methods to include phase contrast and coherent effects in Monte Carlo simulations have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…There is a limited number of computational studies in the field of phase-contrast grating imaging reported in the literature [19][20][21][22][23][24]. All these studies are based on the use of simple objects, such as spheres and cylinders, and aim at proof of concept and optimisation of dose and imaging parameters.…”
Section: Introductionmentioning
confidence: 99%